Clinical descriptors for the recognition of central sensitization pain in patients with knee osteoarthritis. Issue 23 (6th November 2018) - Lluch, Enrique; Nijs, Jo; Courtney, Carol A.; Rebbeck, Trudy; Wylde, Vikki; Baert, Isabel; Wideman, Timothy H.; Howells, Nick; Skou, Søren T.
Abstract: Background: Despite growing awareness of the contribution of central pain mechanisms to knee osteoarthritis pain in a subgroup of patients, routine evaluation of central sensitization is yet to be incorporated into clinical practice. Aim: The objective of this perspective is to design a set of clinical descriptors for the recognition of central sensitization in patients with knee osteoarthritis that can be implemented in clinical practice. Methods: A narrative review of original research papers was conducted by nine clinicians and researchers from seven different countries to reach agreement on clinically relevant descriptors. Results: It is proposed that identification of a dominance of central sensitization pain is based on descriptors derived from the subjective assessment and the physical examination. In the former, clinicians are recommended to inquire about intensity and duration of pain and its association with structural joint changes, pain distribution, behavior of knee pain, presence of neuropathic-like or centrally mediated symptoms and responsiveness to previous treatment. The latter includes assessment of response to clinical test, mechanical hyperalgesia and allodynia, thermal hyperalgesia, hypoesthesia and reduced vibration sense. Conclusions: This article describes a set of clinically relevant descriptors that might indicate the presence of central sensitization in patients with knee osteoarthritis in clinical practice. Although based on research data, the descriptors proposed in this review require experimental testing in future studies. Implications for Rehabilitation: Laboratory evaluation of central sensitization for people with knee osteoarthritis is yet to be incorporated into clinical practice. A set of clinical indicators for the recognition of central sensitization in patients with knee osteoarthritis is proposed. Although based on research data, the clinical indicators proposed require further experimental testing of psychometric properties.